Effects of repetition exercise training on vascular endothelial function in healthy men - Yasuaki Tamura; Hajime Miura; Kenichi Deguchi; Yuji Hashimoto; Junji Deguchi; Ayako Murakami; Mizuki Ishikawa (Japanese Society of Physical Fitness and Sports Medicine, 2022)
High-intensity interval training improves the vascular endothelial function better than moderate-intensity continuous training. However, few studies have examined the effects of repetition training consisting of high-intensity exercise, followed by complete rest, on arterial function. We performed this study to investigate the effects of repetition training of high-intensity exercise on the vascular endothelial function determined by flow-mediated vasodilation. Twenty healthy male participants were randomized and stratified into two training groups, one group performed moderate-intensity continuous training (n = 10) while another performed repetition training of high-intensity exercise (n = 10). Both groups exercised 3 times a week for 6 weeks. Before and after each training protocol, the vascular endothelial function of the right brachial artery was assessed by flow-mediated vasodilation. In the moderate-intensity continuous training group, flow-mediated vasodilation changed 9.92 ± 2.45% to 10.58 ± 2.93% (ns). In the repetition training of high-intensity exercise group, flow-mediated vasodilation changed 7.26 ± 1.46% to 8.58 ± 1.22% (p < 0.05). A greater increase in vascular endothelial function was observed in high-intensity repetition training compared to moderate-intensity continuous training. These results suggest the possible effect of repetition training on the prevention of cardiovascular disease.